Bioavailability of selenium from different dietary sources in yellowtail kingfish (Seriola lalandi) - Le, K.; Fotedar, Ravi (Elsevier BV, 2013)
Different forms of selenium (Se) were supplemented to a fishmeal-based diet to investigate the digestibility and bioavailability of Se in yellowtail kingfish (Seriola lalandi). Five groups of fish in triplicate were fed a basal diet (containing 3.31 mg/kg Se) either unsupplemented or supplemented with 2 mg/kg Se from selenite, selenocystine (SeCys), selenomethionine (SeMet) or Se-yeast for 6 weeks. The basal unsupplemented diet resulted in significantly lower weight gain, red blood cell glutathione peroxidase (GPx) and bactericidal activities than the supplemented diets. Muscle Se concentration was increased by Se supplementation from SeCys, SeMet or Se-yeast, but not selenite. There was no difference in GPx activity of fish fed with any supplemented diets. The bioavailability of Se from SeMet and Se-yeast was similar for all measurements. The most digestible sources of Se were from SeMet and Se-yeast, whereas the least was from fishmeal. Se from SeMet or Se-yeast produced more weight gain, higher Se accumulation in muscle tissues and bactericidal activity in yellowtail kingfish than Se from SeCys or selenite. This study shows that SeMet and Se-yeast are the most bioavailable sources of Se to yellowtail kingfish and are recommended to be supplemented to fishmeal-based formulated diets for yellowtail kingfish.